Problematika penyelenggaraan program literasi informasi bagi sivitas akademika di lingkungan UIN Syarif Hidayatullah Jakarta - Nuryudi Nuryudi (Al Maktabah, 2013)
The objective of this research is to understand the real problems in terms of information literacy program conducted in UIN Syarif Hidayatullah Jakarta libraries which is focusing in three aspects: facilities for accessing electronic resources, user particiption and librarian roles. Problems identified from these aspects are connected to the avalilable electronic resources in this campus. This study uses descriptive-qualitative method combined with quantitative one for some extent. Three libraries had been taken as the objects: the main Library, FITK and FKIK library. The collection of data was conducted by direct observation to the sites, distributing quesioners and interview to nine librarians, and giving quesioners with open questions to twenty two informans of students writing their undergraduate theses. From the research results, it can be seen that although the program of information literacy service has been a part of Indonesian National Standard on librarianship those all libraries haven’t yet conducted the program. Such program they have held in library is a library orientation for new students in new academic year. Although, the facilities have already been phisically installed, the libraries haven’t yet able to optimally support the information literacy instruction because the online network doesn’t have enough capabilities and isn’t stable. As an impact the accessability of online information resources has problems. Many students have unpotential skills of information literacy, and they show a great enthusiasm for the insructional information lieracy. Meanwhile, the available human resources on duty aren’t ready for conducting the project because lack of quantities and qualifications for related tasks.